2020
DOI: 10.1155/2020/6835814
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effect of Foot Massage with Grape Seed Oil and Sweet Almond Oil on Physiological Leg Edema in Primigravidae: A Randomized Clinical Trial

Abstract: Background. Leg edema is a prevalent problem in pregnancy causing activity restrictions for pregnant women. This study was performed to compare the effect of foot massage using grape seed oil and sweet almond oil on physiological leg edema. Methods. A randomized clinical trial was conducted on 90 primigravidae referred to public health centres of Zahedan, Iran. The participants’ gestational age was 30–40 weeks. The study was conducted from August 2016 to November 2017. The participants were randomly assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…More recently [52, 53], it has been reported that SAO has benefits in the treatment of striae itch. These findings correlate with other pruritic conditions involving leg oedema [5, 54] and haemodialysis patients [55, 56]. EPO has been reported to be successful in the prevention of xerotic cheilitis in acne patients being treated with isotretinoin [57].…”
Section: Dermato‐cosmetic Effectssupporting
confidence: 65%
“…More recently [52, 53], it has been reported that SAO has benefits in the treatment of striae itch. These findings correlate with other pruritic conditions involving leg oedema [5, 54] and haemodialysis patients [55, 56]. EPO has been reported to be successful in the prevention of xerotic cheilitis in acne patients being treated with isotretinoin [57].…”
Section: Dermato‐cosmetic Effectssupporting
confidence: 65%
“…Also, one study compared the effects of massage with grape seed oil with sweet almond oil. In terms of analyzed outcomes, there were substantial differences between the assessed trials (9,(21)(22)(23)(24)(25)(26). The trials had a high risk of performance and detection bias and were essentially unclear for selection bias.…”
Section: Resultsmentioning
confidence: 99%
“…The non-pharmacological therapies that we investigated in this study included foot massage, wearing compression stocking and special footwear, immersion in water, feet elevation and resting. Various studies have shown the effective role of foot massage in reducing lower extremity edema in pregnant women (4,25,26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in a double‐blind clinical trial study, sweet almond oil in creams was more effective than the base cream at ameliorating the itching of striae and preventing its progression in 160 nulliparous women (Hajhashemi et al., 2018). More recently, a randomized clinical trial showed positive effects of foot massage with sweet almond oil on leg edema resulting from pregnancy (Navaee & Rakhshkhorshid, 2020). Similarly, foot massage with almond oil was found to be effective in reducing fatigue and improving the quality of life in patients undergoing hemodialysis (Habibzadeh et al., 2020).…”
Section: Potential Health Benefits Of Almond Oilmentioning
confidence: 99%